2017
DOI: 10.1103/physrevb.96.125201
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of valley polarization and dynamic nuclear polarization in 2D transition metal dichalcogenides

Abstract: The interplay of Ising spin-orbit coupling and non-trivial band topology in transition metal dichalcogenides (TMDs) produces anomalous transport and optical properties that are very different from a regular 2D electron gas. The spin-momentum locking of optically excited carriers near a valley point can give rise to an anomalous spin-valley Hall current under the application of an in-plane electric field. TMDs also exhibit strong electronnuclear hyperfine interactions, but their effect on spin-valley-locked cur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Recently, there are proposals to optically control the entanglement of electron and nuclear spins in TMDC monolayers via intervalley terms of the hyperfine interaction [267][268][269] . It has been argued that similar to the case of electron and hole hyperfine interactions in III-V semiconductors 270,271 , they are of short range nature in TMDCs as well.…”
Section: Valley Polarization and Coherence In Magnetic Fieldsmentioning
confidence: 99%
“…Recently, there are proposals to optically control the entanglement of electron and nuclear spins in TMDC monolayers via intervalley terms of the hyperfine interaction [267][268][269] . It has been argued that similar to the case of electron and hole hyperfine interactions in III-V semiconductors 270,271 , they are of short range nature in TMDCs as well.…”
Section: Valley Polarization and Coherence In Magnetic Fieldsmentioning
confidence: 99%
“…TMDs can bring new challenges and peculiarities in the hardly explored field of the electron-nuclear interaction in TMD MLs [53]. Any theoretical description of the effects related to the hyperfine interaction is based on the form of the hyperfine interaction Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
“…However, many works have shown that the state of the bath, and consequently its deleterious effects, can be influenced by driving the electron spin. For example, several experiments have shown that driving can generate dynamic nuclear polarization (DNP), an effect that has been observed in self-assembled QDs [53][54][55][56][57][58][59][60][61][62][63][64] and also in other systems such as gated QDs [65][66][67][68], quantum wires [69] and in bulk materials [70,71], findings that have been supported by a number of theory works [72][73][74][75][76][77][78][79][80][81][82][83][84]. An important example of DNP in self-assembled QDs is the mode-locking experiment of Ref.…”
Section: Introductionmentioning
confidence: 99%